Knee Pain and the Use of Various Types of Footwear—A Review - Chughtai, Morad; Newman, Jared M.; Akil, Samuel; Khlopas, Anton; Sultan, Assem A.; Sodhi, Nipun; Bhave, Anil; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2018)
Knee pain is a highly prevalent condition in the United States with multiple etiologies, with two of the most common sources being osteoarthritis (OA) and patellofemoral pain (PFP). These conditions can lead to reduced physical function and a poor quality of life. Various modalities have been used to decrease the amount of knee pain that individuals' experience; however, they are not always successful and can be expensive. Several studies have reported on specialized footwear for symptomatic alleviation of conditions that affect the knee, this is because it has been theorized that certain footwear can alter the forces placed by muscles on lower-extremity joints, and can potentially alleviate pain by reducing the load placed on the joint. Therefore, the purpose of this study was to review the current literature on the use of various types of footwear used in patients who suffer from knee pain. Specifically, we evaluated: (1) knee OA and (2) PFP and the effect that different footwear has on patients' symptoms. Multiple different types of footwear and orthosis were utilized to treat patients with chronic knee pain. However, the results from reported outcomes by different studies are conflicting, which warrant further studies. Nevertheless, there are enough positive results to view this as a potential major modality to utilize for the treatment of knee OA.
Keywords: knee pain; footwear; patellofemoral pain; osteoarthritis; orthosis